Composition of the organic compounds of different peat types from the Southern taiga subzone of Western Siberia - Serebrennikova, Olga V.; Russkikh, Irina V.; Strelnikova, E. B.; Kharanzhevskaya, Yulia A.; Fedorov, D. V. (Solid fuel chemistry)
Acyclic (n-alkanes, n-alkan-2-ones, fatty acids, methyl esters of fatty acids, n-aldehydes, squalene, phyton, and phytol isomers) and cyclic (series of di- and triterpenoids, steroids, and tocopherols, phytonadione, and dihydroactinidiolide) organic compounds, many of which are biologically active, in peat samples raised bogs and fens of the southern taiga subzone of Western Siberia were studied using gas chromatography-mass spectrometry. Acyclic structures, among which n-alkan-2-ones were predominant, dominated in sedge and sedge-hypnum peat in contrast to Sphagnum peat, in which n-alkanes predominated. The distribution of pentacyclic triterpenoids, n-alkanes, n-alkan-2-ones, and methyl esters of fatty acids was largely determined by the botanical composition of peat.